2015
DOI: 10.1080/15438627.2015.1076416
|View full text |Cite
|
Sign up to set email alerts
|

Muscle damage produced during a simulated badminton match in competitive male players

Abstract: The purpose of the study was to assess the occurrence of muscle damage after a simulated badminton match and its influence on physical and haematological parameters. Sixteen competitive male badminton players participated in the study. Before and just after a 45-min simulated badminton match, maximal isometric force and badminton-specific running/movement velocity were measured to assess muscle fatigue. Blood samples were also obtained before and after the match. The badminton match did not affect maximal isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
3
22
1
1
Order By: Relevance
“…Later, in a group of UK professional footballers of the Premier league and Championship, 5% of the players had moderate-severe irreversible periodontal disease [ 4 ]. Recently, a study in young footballers, revealed an association between BOP and PPD with increased serum creatine kinase levels [ 23 ], a commonly used hallmark to purview muscle injury [ 24 , 25 ]. However, none of these studies have assessed players using up-to-date case definitions (EFP/AAP 2018), but rather clinical measures such as BOP or PPD, and the assessment for associations with nutritional, anthropometric items and past history of injuries are completely novel.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in a group of UK professional footballers of the Premier league and Championship, 5% of the players had moderate-severe irreversible periodontal disease [ 4 ]. Recently, a study in young footballers, revealed an association between BOP and PPD with increased serum creatine kinase levels [ 23 ], a commonly used hallmark to purview muscle injury [ 24 , 25 ]. However, none of these studies have assessed players using up-to-date case definitions (EFP/AAP 2018), but rather clinical measures such as BOP or PPD, and the assessment for associations with nutritional, anthropometric items and past history of injuries are completely novel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the better efficiency of movement executed by skilled players is expected to reduce fatigue and impact levels to the body [ 9 , 15 , 42 ]. Thus, studying physiological profiles, muscle activation and neuromuscular control should be investigated further to identify the differences among playing levels [ 4 , 12 , 21 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Racket sports seem to lead to relevant acute responses on the organism [ 19 , 20 ]. Some authors have previously reported more delayed onset muscle soreness (DOMS) and reduced maximum voluntary contractions (MVC) after several tennis matches [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have previously reported more delayed onset muscle soreness (DOMS) and reduced maximum voluntary contractions (MVC) after several tennis matches [ 19 ]. In simulated badminton matches, changes in hemoglobin and hematocrit levels have been found [ 20 ]. In other racket sports, alterations to neuromuscular function have also been noted after playing matches [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%